The Use of Project-Based Learning to Improve Vocabulary Among Eighth-Grade Students of Mts Nurul Iman Ujan Rintis - Rusdan Bakri; Lalu Abdul Khalik; Ria Hendriani (Tirai Edukasi : Jurnal Pendidikan, 2025)
This research aimed to determine the effect of Project-Based Learning (PBL) in improving the vocabulary skills of eighth-grade students of MTs Nurul Iman Ujan Rintis. This study was motivated by the observation that students often rely on traditional learning methods, which can lead to low motivation and a temporary retention of vocabulary. This research used a quantitative pre-eksperimental design with a one-group pre-test and post-test approach. The sample consisted of 19 students from grade VIII A, comprising 8 males and 11 females. The findings show a significant improvement in students’ vocabulary scores, with the average score increasing from 43.15 in the pre-test to 63.94 in post-test. The paired sample t-test confirmed the significance of the results, with a t-test value of -9.572 and a significance value of 0.000 (<0.05). These results indicate that PBL is an effective method for enhancing students’ vocabulary mastery and that students were more motivated and enthusiastic about learning through projects.